PENGAWASAN KEPOLISIAN DALAM MENGATASI KEMACETAN LALU LINTAS DI KOTA PEKANBARU TAHUN 2017 - Pancasila, Ari Sakti; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The city of Pekanbaru has a densely populated population of more than one million people. Along with the development of the city of Pekanbaru to become a Metropolitan City, it is inseparable from various problems that arise, namely the problem of Traffic congestion. The Problem of Traffic Congestion is a problem that does not resolve every year. This is caused by the Police not yet maximal in overcoming Traffic Congestion in the City of Pekanbaru. In this case, of course, the public spotlight on the performance of the Police in overcoming the problem of Traffic Congestion in the City of Pekanbaru. The formulation of the problem in this study is Why has Police supervision not been maximized in overcoming Traffic Congestion in Pekanbaru City in 2017? This study aims to determine the oversight carried out by the police in dealing with traffic congestion in Pekanbaru City in 2017, to find out the inhibiting factors of the police in handling traffic congestion in Pekanbaru City in 2017. This research is a descriptive study using a qualitative descriptive approach. The data collection technique in this study is to use interview techniques with the number of informants as many as 9 people and using documentation techniques can be in the form of writing, images or monumental works from someone. To explain the problems in this study used qualitative methods to show research that produces qualitative data, namely data that cannot be realized in the form of numbers, but in the form of an explanation that describes certain conditions, processes, events. The results of the study concluded that police supervision in overcoming traffic congestion in the city of Pekanbaru in 2017 is still not optimal. This is still the existence of factors that inhibit the police in handling traffic congestion is the construction of roads, an increase in the number of vehicles, traffic light, illegal parking, and street vendors. In this case the author considers that the Pekanbaru Police Satlantas is not as expected, there are still many shortcomings and problems faced by the Pekanbaru Police Satlantas and the form of actions taken by the Pekanbaru Police Satlantas has not run optimally. Keywords: Police Supervision, Traffic Congestion in Pekanbaru City